2017
DOI: 10.1089/ars.2016.6630
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Regulates Skeletal Muscle Fatigue, Fiber Type, Microtubule Organization, and Mitochondrial ATP Synthesis Efficiency Through cGMP-Dependent Mechanisms

Abstract: Aim: Skeletal muscle nitric oxide-cyclic guanosine monophosphate (NO-cGMP) pathways are impaired in Duchenne and Becker muscular dystrophy partly because of reduced nNOSl and soluble guanylate cyclase (GC) activity. However, GC function and the consequences of reduced GC activity in skeletal muscle are unknown. In this study, we explore the functions of GC and NO-cGMP signaling in skeletal muscle. Results: GC1, but not GC2, expression was higher in oxidative than glycolytic muscles. GC1 was found in a complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 74 publications
0
38
0
Order By: Relevance
“…Arg is the unique natural precursor in the biosynthesis of NO by NOS (19) . A large number of studies showed that NO or NOS plays an important role in regulating muscle fibre type composition (20)(21)(22) . In the present study, we found that dietary supplementation of 1‱0 % Arg increased NO content, NOS activity, protein expression of MyHC I and mRNA expressions of type I muscle fibres-related genes (MyHC I, Tnni1, Tnnc1 and Tnnt1) in longissimus dorsi muscle of weaning piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Arg is the unique natural precursor in the biosynthesis of NO by NOS (19) . A large number of studies showed that NO or NOS plays an important role in regulating muscle fibre type composition (20)(21)(22) . In the present study, we found that dietary supplementation of 1‱0 % Arg increased NO content, NOS activity, protein expression of MyHC I and mRNA expressions of type I muscle fibres-related genes (MyHC I, Tnni1, Tnnc1 and Tnnt1) in longissimus dorsi muscle of weaning piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the initial animal studies of riociguat activity in adolescent rats and mice showed various degrees of bone resorption and remodeling in the femur and tibia [ 17 ], clinical studies in adults did not show any adverse effect on bones. In addition, we have reported normal bone densities in mice lacking GC1 demonstrating that GC1 does not play an important role in specifying bone density [ 66 ]. Regardless, the FDA has raised a concern for a future reference for use of riociguat in pediatric patients, even when conducting clinical trials [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on tissue localization, NO regulation is different. For instance, in brown adipose or muscle tissue, several studies with eNOS knockout mice show that NO/cGMP pathway controls mitochondrial biogenesis [109,110]. However, in endothelial cells, NO is necessary to migration cells [111].…”
Section: Tissue-specificmentioning
confidence: 99%